THE USE OF BAMBOO DANCING TECHNIQUE TO IMRPOVE STUDENTS’ SPEAKING SKILL IN INTERPERSONAL CONVERSATION (A Classroom Action Research at Grade VII Students of SMP IT Insan Cendekia Semarang in the Academic Year of 2014/2015) (ELT Forum: Journal of English Language Teaching, 2015)
Mostly students of Junior High School have difficulties in their speaking skill, especially in interpersonal conversation. It is because they have to concern with the material and also the practice of the conversation itself. So, some techniques should be carried out to make speaking easier and interesting. One of the techniques to teach speaking is bamboo-dancing technique which is one of cooperative learning technique, in which students are placed in two lines to see each other and make conversation (Suprijono (2009:98)). The aim of this study is to find out how bamboo-dancing technique can be implemented in improving students’ skill to master interpersonal conversation. In order to achieve the objectives, an action research was designed and carried out in this study. The participants of this study were 28 students of class VII B of SMP IT Insan Cendekia Semarang in the academic year of 2014/2015. Questionnaires, observation guide, and speaking tests were used as the instruments for collecting the data. The analysis results of the first and second questionnaires showed that bamboo-dancing technique was useful to most of students of SMP IT Insan Cendekia Semarang to improve their learning motivation and interesting in interpersonal conversation. Their perception was changed positively after having the treatment. It meant that the use of bmboo-dancing technique could ease their problem in speaking in English especially interpersonal conversation. The results of the study showed significant improvement of the students’ achievement in mastering interpersonal conversation. It is proven by the average results in every test; pre cycle test (67), cycle 1 test (73), and post cycle test (79). Moreover, the result of the observation guide showed that bamboo-dancing technique changed the students’ learning behaviour being better than before. Based on the results of those research instruments, it can be concluded that the use of bamboo-dancing technique as learning technique gives the improvement of students’ speaking skill in interpersonal conversation in terms of motivation, attitude and mastery.